2007
DOI: 10.1080/17470910701392024
|View full text |Cite
|
Sign up to set email alerts
|

The self as a moral agent: Linking the neural bases of social agency and moral sensitivity

Abstract: The human brain is inherently able to understand the world in moral ways, endowing most of us with an intuitive sense of fairness, concern for others, and observance of cultural norms. We have argued that this moral sensitivity ability depends on a sophisticated integration of cognitive, emotional, and motivational mechanisms, which are modulated by individual experience in different cultural milieus. Different lines of investigation on agency and morality have pointed to overlapping neural systems. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
159
4
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(178 citation statements)
references
References 71 publications
10
159
4
5
Order By: Relevance
“…In addition, self-agency related to moral functioning shared neural substrates with the CMS [42]. Given these previous studies, we expect that there is significant relationship between the neural correlates of moral functioning and selfhood-related processes.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, self-agency related to moral functioning shared neural substrates with the CMS [42]. Given these previous studies, we expect that there is significant relationship between the neural correlates of moral functioning and selfhood-related processes.…”
Section: Introductionmentioning
confidence: 82%
“…This hypothesis originates from previous neuroimaging studies utilizing similar dilemma task conditions [25,26,51]. Moral-personal dilemmas are more likely to induce significant activity in regions associated with emotion (e.g., MPFC, orbitofrontal cortex (OFC), superior-temporal sulcus (STS), insula [42,[51][52][53][54][55]) compared to moral-impersonal dilemmas, because the former strongly induce negative immediate emotional responses among subjects. On the other hand, previous studies have shown that in the moral-impersonal condition, regions associated with cognition, such as mental calculation (e.g., parietal lobule), will show significantly increased activity [25,26,51,56].…”
mentioning
confidence: 99%
“…Although emotions were induced indirectly by the reliving of respective affective experiences from the past, without referring to the specific emotion's name, the subjective ratings clearly indicate that this method of inducing the target emotions during scanning was highly efficient. In this way, our study goes beyond previous neuroimaging experiments that focused primarily on judgmental rather than affective aspects of moral processing, including guilt-related processing, by presenting subjects during scanning with scripts of hypothetical scenarios of prototypical social or moral transgressions (Takahashi et al 2004;Moll et al 2007;Kedia et al 2008;Burnett et al 2009). These studies found activations in several brain regions associated with social cognition, ToM, and emotional processing, generally shared with other moral conditions, but critically, they did not report an involvement of the 2 specific prefrontal regions related to guilt here, confirming our interpretation that these regions are linked to an individual affective experience of guilt that probably would not be induced in sufficient intensity by reading hypothetical scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…During fMRI, participants were later prompted by their own keywords and asked to relive vividly the emotion experienced during the target event. Unlike other paradigms targeting more evaluative moral processes by asking participants to judge hypothetical scripts of social or moral actions (e.g., Takahashi et al 2004;Moll et al 2007;Kedia et al 2008;Takahashi et al 2008;Burnett et al 2009), this procedure allows the induction of a genuine, personally relevant feeling of guilt.…”
Section: Introductionmentioning
confidence: 99%
“…(iii) Self-related processing, episodic memory, social cognition and sense of agency: Topics of inner rumination, reflection, motivation have been subsumed under the heading of default mode function, using findings from task-based studies to support the specialized roles of the implicated regions (Spreng et al, 2009;Goldberg et al, 2008;Schilbach et al, 2008;Moll et al, 2007). Much support has been drawn from the rationale that the content of mind-wandering is composed of episodic memory, prospection, and the consideration of social relationships.…”
Section: History Of Resting State Research: Lineage 1 -'Default Mode'mentioning
confidence: 99%